KAJIAN PEMANFAATAN METODE SEVERE HAIL INDEX SECARA SPASIAL UNTUK DETEKSI KEJADIAN HUJAN ES DI JAWA BARAT - I Made Agus Satya (Komunikasi Fisika Indonesia, 2022)
Hail is precipitation that is detrimental to the community, occurs in a short time, and is very local. It becomes a challenge to detect and give early warning. One method known to detect hail is the severe hail index (SHI) and its derivative product, the probability of severe hail (POSH). Utilize weather radar, the method detects by taking the value of the kinetic energy flux of hail by calculating the integration of the reflectivity weight and temperature flux from the freezing level to a temperature of -20ºC. This study aims to examine the spatial use of SHI and POSH methods to detect hail events in the West Java region. The results of SHI value obtained for 350 Jm-1s-1– 400 Jm-1s-1 for Depok and 280 Jm-1s-1– 320 Jm-1s-1 for Bogor, which met the threshold of average hail threshold of 373 Jm-1s-1. Then POSH obtained a 70% – 80% probability for Depok and Bogor. Meanwhile, for Bandung, the SHI value is 12 Jm-1s-1– 14 Jm-1s-1 and 0% for POSH. Concluded that hail detection utilizing SHI and POSH methods effectiveness, influenced by the distance to the radar so it requires other additional methods such as RGB Composite from satellite imagery as support. Spatial calculations can also reduce value bias and give more accurate location occurrences.